Quality of life and body image of patients with urinary disorders - Gardênia Lima Gurgel do Amaral; Kleynianne Medeiros de Mendonça Costa; Charlene Maria Ferreira de Lima; Tânia Arena Moreira Domingues; Dulce Aparecida Barbosa; Angélica Gonçalves Silva Belasco (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to assess the quality of life and body image of men with difficulty urinating and indwelling urinary catheter users, integrating the socio-demographic, economic and morbidity variables. Method: a cross-sectional analytical study with 64 male patients with urinary problems. Three questionnaires were used for data collection: one containing sociodemographic, economic and morbid data, the Medical Outcome Study 36-item short-form health survey to analyze quality of life, and the Body Dysmorphic Examination, which assesses body image. T-test, Mann-Whitney, Pearson, Spearman, Linear Regression and Stepwise were used. Results: quality of life and body image were compromised in both groups, affecting emotional aspects, with a high degree of body dissatisfaction and altered physical and social adversity. Conclusion: changes in patients' quality of life and body image were observed, confirming the need for improvement in care.